Shifts in cranial integration associated with ecological specialization in pinnipeds (Mammalia, Carnivora) - Randau, Marcela (R Soc Open Sci, 2019)
Patterns of trait integration reflect the underlying genetic and developmental architecture of morphology and significantly influence the direction of evolution. Nevertheless, the relationship between integration and disparity is complex and unlikely to be uniform across large phylogenetic and ecological scales. To date, there are little data comparing patterns of integration across major ecological transitions, limiting understanding of the processes driving changes in trait integration and their consequences. Here, we investigated patterns of cranial integration and disparity across pinnipeds, three closely related carnivoran families that have undergone a secondary adaptation to the aquatic niche with varying levels of ecological differentiation. With a three-dimensional geometric morphometric dataset of 677 specimens spanning 15 species, we compared five models of trait integration, and examined the effects of sexual dimorphism and allometry on model support. Pinnipeds varied greatly in patterns of cranial integration compared to terrestrial carnivorans. Interestingly, this variation is concentrated in phocids, which may reflect the broader range of ecological and life-history specializations across phocid species, and greater independence from the terrestrial habitat observed in that group, relative to otariids. Overall, these results indicate that major ecological transitions, and presumably large changes in selection pressures, may drive changes in phenotypic trait integration.